Diamond–Blackfan anemia with mandibulofacial dystostosis is heterogeneous, including the novel DBA genes TSR2 and RPS28. Issue 9 (18th June 2014) - Gripp, Karen W.; Curry, Cynthia; Olney, Ann Haskins; Sandoval, Claudio; Fisher, Jamie; Chong, Jessica Xiao‐Ling; UW Center for Mendelian Genomics; Pilchman, Lisa; Sahraoui, Rebecca; Stabley, Deborah L.; Sol‐Church, Katia
<x xml:space="preserve">Abstract</x> Patients with physical findings suggestive of Treacher Collins syndrome (TCS) or mandibulofacial dysostosis (MFD) and macrocytic anemia diagnostic of Diamond–Blackfan anemia (DBA) have been reported. Disease‐causing genes have been identified for TCS and other MFDs. Mutations in several ribosomal protein genes and the transcription factor GATA1 result in DBA. However, no disease‐causing mutation had been identified in the reported patients with the combination of TCS/MFD and DBA phenotype, and we hypothesized that pathogenic mutations in a single gene could be identified using whole exome analysis. We studied probands from six unrelated families. Combining exome analysis and Sanger sequencing, we identified likely pathogenic mutations in 5/6 families. Two mutations in unrelated families were seen in RPS26, the known DBA10 gene. One variant was predicted to affect mRNA splicing, and the other to lead to protein truncation. In another family a likely pathogenic X‐linked mutation affecting a highly conserved residue was found in TSR2, which encodes a direct binding partner of RPS26. De novo mutations affecting the RPS28 start codon were found in two unrelated probands, identifying RPS28 as a novel disease gene. We conclude that the phenotype combining features of TCS with DBA is genetically heterogeneous. Each of the pathogenic variants identified is predicted to impede ribosome biogenesis, which in turn could result in altered cell growth and proliferation, causing abnormal embryologic development, defective erythropoiesis and reduced growth. The phenotype combining TCS/MFD and DBA is highly variable, overlaps with DBA and lies within the phenotypic spectrum of ribosomopathies. © 2014 Wiley Periodicals, Inc.